A Kinetic View of Membrane Traffic Pathways Can Transcend the Classical View of Golgi Compartments - Pantazopoulou, Areti; Glick, Benjamin S. (Frontiers in Cell and Developmental Biology, 2019)
A long-standing assumption is that the cisternae of the Golgi apparatus can be grouped into functionally distinct compartments, yet the molecular identities of those compartments have not been clearly described. The concept of a compartmentalized Golgi is challenged by the cisternal maturation model, which postulates that cisternae form de novo and then undergo progressive biochemical changes. Cisternal maturation can potentially be reconciled with Golgi compartmentation by defining compartments as discrete kinetic stages in the maturation process. These kinetic stages are distinguished by the traffic pathways that are operating. For example, a major transition occurs when a cisterna stops producing COPI vesicles and begins producing clathrin-coated vesicles. This transition separates one kinetic stage, the “early Golgi,” from a subsequent kinetic stage, the “late Golgi” or “trans–Golgi network (TGN).” But multiple traffic pathways drive Golgi maturation, and the periods of operation for different traffic pathways can partially overlap, so there is no simple way to define a full set of Golgi compartments in terms of kinetic stages. Instead, we propose that the focus should be on the series of transitions experienced by a Golgi cisterna as various traffic pathways are switched on and off. These traffic pathways drive changes in resident transmembrane protein composition. Transitions in traffic pathways seem to be the fundamental, conserved determinants of Golgi organization. According to this view, the initial goal is to identify the relevant traffic pathways and place them on the kinetic map of Golgi maturation, and the ultimate goal is to elucidate the logic circuit that switches individual traffic pathways on and off as a cisterna matures.